An Atom‐Pair Design Strategy for Optimizing the Synergistic Electron Effects of Catalytic Sites in NO Selective Reduction. Issue 52 (28th November 2022) - Qu, Weiye; Yuan, Haiyang; Ren, Zhouhong; Qi, Jizhen; Xu, Dongrun; Chen, Junxiao; Chen, Liwei; Yang, Huagui; Ma, Zhen; Liu, Xi; Wang, Haifeng; Tang, Xingfu
Abstract: Effective adsorption and speedy surface reactions are vital requirements for efficient active sites in catalysis, but it remains challenging to maximize these two functions simultaneously. We present a solution to this issue by designing a series of atom‐pair catalytic sites with tunable electronic interactions. As a case study, NO selective reduction occurring on V1 −W1 /TiO2 is chosen. Experimental and theoretical results reveal that the synergistic electron effect present between the paired atoms enriches high‐energy spin charge around the Fermi level, simultaneously rendering reactant (NH3 or O2 ) adsorption more effective and subsequent surface reactions speedier as compared with single V or W atom alone, and hence higher reaction rates. This strategy enables us to rationally design a high‐performance V1 −Mo1 /TiO2 catalyst with optimized vanadium(IV)‐molybdenum(V) electronic interactions, which has exceptional activity significantly higher than the commercial or reported catalysts. Abstract : Reactant adsorption and surface reactions are two key steps in heterogeneous catalysis but the simultaneous optimization of these two variables remains challenging. These two key steps were optimized concomitantly in a model reaction—NO selective reduction—by designing a series of atom‐pair active sites with a strong electronic synergy.